A retrospective study on acquired demyelinating diseases in children - Gajre, Mona P.; Sarkate, Akash D.; Joshi, Swarali S.; Adhikari, Arpita D.; Garg, Ankur (International Journal of Contemporary Pediatrics, 2023)
Background: Acquired demyelinating diseases (ADS) соnstitute а heterogeneous grоuр of central nervous system disorders of autoimmune origin that causes significant physical and cognitive disabilities. Early recognition and prompt management causes significant improvement in acute episodes of demyelinating disorders. Methods: 33 children diagnosed with demyelinating disorders at Lokmanya Tilal municipal medical college and hospital in Mumbai were enrolled. The study was conducted between January 2013 and November 2022. Demographic data, clinical profile, CSF study, serum antibody, radiological findings were collected and results were analyzed. Statistical Data was analysed using statistical software GraphPad in Stat.V3.0. Data were presented in tables and figures whenever needed. P value <0.05 considered as significant. Results: Of 33 patients, 21 (63%) were cases of acute disseminated encephalomyelitis (ADEM), 6 (18.1%) of transverse myelitis (TM), 1 case of ADEM + TM (3%), 3 (9%) of neuromyelitis optica, 1 (3%) of Optic neuritis and 1 (3%) of multiple sclerosis. ADEM patients presented with encephalopathy and multifocal neurological deficits, 40% were MOG positive. Two patients were of multiphasic ADEM. Patients of transverse myelitis had paraparesis or quadriparesis and sensory + bladder involvement. Patients with NMO presented with bilateral visual impairment with limb weakness and bladder involvement. Steroids were the primary treatment, 3 patients (9%) required intravenous immunoglobulin (IVIG) and 1 (3%) patient received plasma exchange therapy. Conclusions: ADEM is the most common ADS. Early diagnosis and management with steroids therapy improves outcome in most of the patients. Non response to steroids warrants second line treatment options like IV Immunoglobulin (IVIG) or Therapeutic plasma exchange.